Implementing Snack Food Composition Label Analysis for Numeracy Learning in Elementary School: A Study in Teacher Professional Education - Siti Maryam Rohimah; Dadang Iskandar; Eggie Nugraha; Taufiqulloh Dahlan; Yuni Indriyani; Siti Maryam Rohimah; Dadang Iskandar; Eggie Nugraha; Taufiqulloh Dahlan (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The use of authentic contexts in numeracy learning is important to help prospective elementary school teachers design meaningful and contextual mathematics instruction. However, a gap remains in the literature regarding how prospective teachers perceive the feasibility and potential of authentic context-based numeracy activities. This study aimed to explore how elementary student teachers in a Teacher Professional Education (TPE) program perceive the feasibility and potential of implementing the activity "Analysis of Composition Labels of Snack Foods" as a vehicle for promoting numeracy learning. A descriptive qualitative method was employed, involving 57 TPE students who completed a perception questionnaire following the learning activity. Data triangulation was conducted through semi-structured interviews and classroom observations. Quantitative data were analyzed using descriptive statistics, while open-ended responses were analyzed through content analysis using NVivo 12. Findings revealed that 92.98% of participants regarded the activity as feasible and relevant for initial numeracy assessment, recognizing its contextual nature, engaging quality, and ease of implementation. The activity was found to support the development of cognitive and practical skills, including proportional reasoning, unit conversion, critical thinking, and data interpretation. Furthermore, the activity demonstrated applicability across multiple elementary school subjects, reflecting its potential as a cross-curricular instructional approach. These findings suggest that snack food composition label analysis is a feasible and beneficial learning activity that can be meaningfully integrated into core elementary mathematics topics, including fractions, measurement, and data presentation.